THE POSITIONS OF THE СONSTITUTIONAL СOURT OF THE REPUBLIC OF KAZAKHSTAN ON THE CALCULATION OF ALIMONY OBLIGATIONS (Journal of actual problems of jurisprudence, 2025)
The study is devoted to the analysis of the implementation of constitutional provisions on the protection of marriage, family, motherhood, fatherhood and childhood through the prism of alimony obligations for the maintenance of children after the dissolution of marriage in the norms of family and executive legislation. During the two years of its existence, the Constitutional Court has repeatedly considered the issues of the constitutionality of legislation on the calculation of alimony. In this regard, the purpose of the preliminary study is to analyze the position of the Constitutional Court of the Republic of Kazakhstan on the legal regulation of alimony legal relations. Namely, the position of the constitutional control body on the accrual of alimony from a parent who does not have a permanent income is being investigated. The study is based on an analysis of the current legislation of the Republic of Kazakhstan on alimony obligations, scientific research on the problems of family relations in Kazakhstan and a number of other countries, statistics provided by government agencies of the Republic of Kazakhstan and reports of authorized authorities. The results revealed the importance of the Constitutional Court's position in correcting the current legislation on alimony obligations. Taking into account the financial and marital status of the parties is an important condition for observing justice and guaranteeing the fulfillment of alimony obligations towards children. It is important that alimony is recognized as an important tool for protecting childhood.Keywords: child protection, alimony obligations, income, net income, Constitutional Court, positions of the Constitutional Court, avoidance of payment of alimony obligations.